Factors affecting the control of budget abuse - Saraswati, Agnes Eka; Setiyawati, Hari (Journal of Contemporary Accounting, 2021)
This research begins with a phenomenon where some government institutions experienced an increase in corruption cases in budget absorption so that it did not reflect the implementation of effective good government governance. This study aims to examine and analyze the effect of implementing an internal control system and the enforcement of good government governance on the level of budget abuse control and its impact on public accountability. This research is quantitative research. Collecting data using a questionnaire to 78 samples from total of 196 employees in the Travel Document Management and Analysis Work Unit at the Directorate of Immigration Traffic. Data analysis using SmartPLS. The results of the study show internal control system and good government governance significant effect on the control of budget abuse. In addition, the control of budget abuse also has a significant effect on public accountability.